The correlation of clinical evaluation with life quality and mental status in a Chinese cohort with dysferlinopathy. (November 2020) - Feng, Xuelin; Liu, Changxia; Xi, Jianying; Sun, Chong; Yue, Dongyue; Zhu, Wenhua; Li, Jing; Liang, Zonghui; Lu, Jiahong; Luo, Sushan
Highlights: This is the first study mainly regarding the mental status and life quality in patients with dysferlinopathy. Declined score in body pain and mental health were of note in female patients. Some patients suffered from depression and anxiety with a high score in PHQ-9/GAD-7. The 6MWT was well-correlated with the severity of depression and most scores in QoL. Abstract : Introduction: Impaired mood and quality of life was common in muscular dystrophies and play an important role in long-term management. Previous studies in dysferlinopathies mainly focused on the genotype-phenotypes correlations. Currently there are very few reports regarding the mental status, life quality and the correlated factors. Methods: A total of 22 patients with dysferlinopathy was recruited and evaluated by 6-minute walking test (6MWT) and adapted-North Star Ambulatory Assessment (a-NSAA). Chinese version of SF-36, PHQ-9, and GAD-7 scale were used to evaluate the Quality of Life (QoL), depression and anxiety. Statistical analysis was applied to investigate the correlation between clinical variables and life quality or mental status. Results: SF-36 evaluation revealed multiple dimensional impairment in dysferlinopathy patients. Declined score in body pain (78.00 vs. 91.23, p = 0.0129) and mental health (56.00 vs.72.88, p = 0.0493) were of note in female patients. Some patients suffered from depression (23%) and anxiety (23%) with a high score in PHQ-9/GAD-7. The 6MWT was well-correlated with the severity of depression and most scores in QoL except Body Pain and Role emotion. Conclusion: The cross-sectional study revealed impaired mental status and life quality in dysferlinopathy, particularly in female patients. The life quality impairment is correlated with the clinical severity.